KEMAMPUAN MENULIS PARAGRAF ARGUMENTASI SISWA KELAS X SMAN 1 KANDIS KABUPATEN SIAK - Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study investigated the ability to write a paragraph argumentation class X SMAN 1 Kandis Siak. This study aims to determine the ability to write a paragraph argumentation class X SMAN 1 Kandis Siak Regency . Writing paragraphs argument from the aspect of unity , cohesion and development . This research is descriptive - quantitative . This research data is data from test-taking ability to write a paragraph argumentation class X SMAN 1 Kandis Siak . Instruments in this research is shaped test write paragraphs argumentation class X SMAN 1 Kandis Siak . The data collection was done by using the test . The population in this study were 177 students with the determination of a sample of 122 students . Data were analyzed with descriptive methods . The validity of the data obtained through the method of data validation . Results of this study of the test results the ability to write a paragraph argumentation class X SMAN 1 Kandis Siak . Viewed from the aspect of understanding the unity of the average values obtained 77.54 with category . Then , from the aspect of cohesion values obtained an average of 67.38 with the medium category . Recently , on the aspect of the development of the average values obtained 53.93 with a low category .Key Words : Paragraph Arguments , Unity , Cohesion , Development .